2010
DOI: 10.1179/146532810x12637745451997
|View full text |Cite
|
Sign up to set email alerts
|

Detection of coronaviruses in children with acute gastroenteritis in Maddina, Saudi Arabia

Abstract: Coronaviruses were commonly identified in children with diarrhoea in Saudi Arabia. Their role in paediatric gastro-enteritis warrants further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…However, the detection rate of each strain of HCoVs varied in different regions, and the detection The age distribution of HCoVs strains in this study was mostly in patients in the age groups below 5 years and equal to or above 60 years old, 31 % and 23.8%, respectively. Our results were in part similar to the result in a previous study that showed that the range of children age infected with HCoVs was 42 months (Kheyami et al, 2010). Another study showed that the age group affected was children less than 2 years old (Risku et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the detection rate of each strain of HCoVs varied in different regions, and the detection The age distribution of HCoVs strains in this study was mostly in patients in the age groups below 5 years and equal to or above 60 years old, 31 % and 23.8%, respectively. Our results were in part similar to the result in a previous study that showed that the range of children age infected with HCoVs was 42 months (Kheyami et al, 2010). Another study showed that the age group affected was children less than 2 years old (Risku et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…In a Slovenia study (Jevsnik et al, 2016), HCoV particles were detected in 8.7% of the tested specimens. Another study in Saudi Arabia (Kheyami et al, 2010) showed a 6% prevalence of HCoVs in AGE patients. A Finnish study (Risku et al, 2010) using molecular methods showed a 2.5% prevalence rate of HCoVs and distributed as follows: 45.5% HCoV-OC43, 27.3% HCoV-HKU1 and 18.2% HCoV-NL63.…”
Section: Discussionmentioning
confidence: 95%
“…55,[58][59][60][61][62][63][64][65] Studies from Argentina and Saudi Arabia respectively found the virus structure in 1.1% and 6% of samples from children with diarrhea. 61,66 The coronavirus morphotype was also found in outbreaks among neonates during manifestations of neonatal necrotizing enterocolitis. 55,65,67 Patients with HIV infection, including some with a characteristic "wasting syndrome,"…”
Section: Evidence From Electron Microscopymentioning
confidence: 99%
“…Reports of the EM findings of coronavirus suggested that the putative pathogen(s) could be identified in outbreak settings of diarrhea 55,58‐65 . Studies from Argentina and Saudi Arabia respectively found the virus structure in 1.1% and 6% of samples from children with diarrhea 61,66 . The coronavirus morphotype was also found in outbreaks among neonates during manifestations of neonatal necrotizing enterocolitis 55,65,67 .…”
Section: Human Coronaviruses As Enteric Pathogensmentioning
confidence: 99%
“…Although seasonal HCoVs only make up a small proportion of these cases in comparison to viruses such as norovirus (NoV), rotavirus (RoV), rhinovirus (RhV) and adenovirus (AdV), it does imply that SARS-CoV-2 is not unusual in inducing GI problems and this symptom may represent a part of its infection cycle (Fig. 3) (Rovida et al, 2013) (Drosten et al, 2013) (Kheyami et al, 2010) (Esper et al, 2010) (Risku et al, 2010).…”
Section: Fecal Shedding Patterns Of Sars-cov-2mentioning
confidence: 99%